Textual Equivalence through Pragmatics and the Semiotics of Culture - Alsharoua, Nabhan Ahmad (2015)
A Master of Arts thesis in Translation and Interpreting MATI (English/Arabic/English) by Nabhan Ahmad Alsharoua entitled, "Textual Equivalence through Pragmatics and the Semiotics of Culture," submitted in May 2015. Thesis advisor is Dr. Basil Hatim. Soft and hard copy available.